CANOPT – Cascaded Network Optimization Package - Bandler, John W.; Rizoniko-Popovic, Jadranka (Communications Research Laboratory, 1974)
This program analyzes and optimizes certain cascaded linear, time-invariant networks in the frequency domain made up of the two-port elements such as resistors, inductors, capacitors, lossless transmission lines, lossless short-circuited and open-circuit transmission line stubs, series and parallel RLC resonant circuits, and microwave allpass C- and D-sections. John W. Bandler was a member of the Communications Research Laboratory from 1970 to 1973, leaving to form the Research Group on Simulation, Optimization and Control.
Report and program package produced by John W. Bandler and Jadranka Rizoniko-Popovic. Program package is written in FORTRAN IV.
Keywords: network optimization; computer-aided design